Inclusão social e as pessoas com deficiência: uma análise na perspectiva crítica - Carvalho, Alfredo Roberto de (2009)
This work is inserted in the perspective of establishing a critic reflection about the proposal of social inclusion and people with disabilities, particularly those people who belong to the exploited social class. On this perspective, the starting point of the analysis is the understanding of the conditionings which took humanity to develop, historically, different practices and conceptions related the this segment, mainly: extermination or abandon, institutionalization, integration, inclusion, mystic and biologic or naïve. On the sequence, it is analyzed the uprising of the inclusive proposal, demonstrating that the mentioned proposal is an answer to the pressures made by excluded and marginalized segments, articulated with the new necessities imposed by capital´s need for expansion. Finally, there are presented and analyzed the main principals which are sustaining this proposal, especially: equal opportunities; respect for the diversity and valorization of the differences; and of concept relativist of knowledge, showing that these same principals have been responding fundamentally to the needs of the actual capitalist´s development model. Along the work, it is sustained the hypothesis that the social inclusion proposal, because it is based on those principals, cannot put itself as an effective instrument to combat the main determinants of the problems historically lived by the people with disabilities, but, on the contrary, it has been used to hide the classist nature of the capitalist society, which, nowadays, constitute the fundamental basis that sustain the whole process of generating inequality, exclusion and marginalization. On the perspective pointed by those principals, the concepts of classes' contradictions are discarded and fights between exploited and explorer are substituted for the proposition of a new attitude facing the social problems, involving changes specially on the formal plan. In order to the fight of people with disabilities can go over and above the denunciation of the traditional practices and conceptions, allowing the comprehension and the confrontation of the real determinants which, historically, have been excluding them, it is necessary that the fight does not remain restricted to the formal/ideal plan. However, this task must involve everyone who can formulate a critical analysis about the problems historically faced by humanity, contributing to put in doubt the conditions of existence of all marginalized segments from the materiality present in some historical moment. This comprehension will allow, surely, the denaturalization of the segregational practices and conceptions related to the people with disabilities, and insert the confrontation against them in the fighting process to overcome the capitalistic mode of production and the construction of a society without explorers and exploited, meaning a new social formation where every individual contributes according to its possibilities and receives according to its needs. That is the society in which can be established the necessary conditions so the defect, by itself, does not make a person with disability the individual who carries it.